2022
DOI: 10.1155/2022/1497748
|View full text |Cite
|
Sign up to set email alerts
|

Will 14-3-3η Be a New Diagnostic and Prognostic Biomarker in Rheumatoid Arthritis? A Prospective Study of Its Utility in Early Diagnosis and Response to Treatment

Abstract: Aim of the Work. To evaluate diagnostic and prognostic capacity of 14-3-3η protein in early RA, investigate its pathogenic and theragnostic role, and find its correlations with disease activity and severity in established RA patients. Subjects and Methods: 80 patients with early RA, 80 patients with established RA, and 80 healthy controls were included in this study. ROC curve analysis of RF, ACCP, and 14-3-3η in early disease was conducted, and serum levels of 14-3-3η were assessed by ELISA and reassessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The study by El-Bakry et al showed that serum sclerostin levels of 267ng/dl, a sensitivity of 96.8%, and a specificity of 66.7% [31] were recorded. In the study by Shawky Alashkar in 2022 conducted on 80 early patients, the sensitivity and specificity of anti-CCP were 68.3%, 95%, and 61.7%, 88.3% for RF antibodies, respectively [35]. The 2019 study by Singh et al in India demonstrated that at a value of 394 pg/ml, the sensitivity was 100%, the specificity was 90%, PPV was 90%, and NPV was 100% to differentiate the group of rheumatoid arthritis patients from the healthy group [24].…”
Section: Discussionmentioning
confidence: 98%
“…The study by El-Bakry et al showed that serum sclerostin levels of 267ng/dl, a sensitivity of 96.8%, and a specificity of 66.7% [31] were recorded. In the study by Shawky Alashkar in 2022 conducted on 80 early patients, the sensitivity and specificity of anti-CCP were 68.3%, 95%, and 61.7%, 88.3% for RF antibodies, respectively [35]. The 2019 study by Singh et al in India demonstrated that at a value of 394 pg/ml, the sensitivity was 100%, the specificity was 90%, PPV was 90%, and NPV was 100% to differentiate the group of rheumatoid arthritis patients from the healthy group [24].…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, a relationship has been shown between disease activity and disease progression and the levels of eta in patients with RA (13,21). 14-3-3η has been detected in the serum and more specifically in the synovial fluid of patients with RA, and it is a valuable marker for the diagnosis of patients and also indicates the severity of the disease and joint destruction (13,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…About (33%) of RA patients are ACPA-seronegative 1 and 30% to 45% are RF seronegative despite the appearance of symptoms 9 . The sensitivity of ACPA and RF in established RA range from 56-80% and 60 to 86% respectively 1,12 . While for early RA, the sensitivity of RF is 57% and its low specificity ranges between 70-85% 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of ACPA and RF in established RA range from 56-80% and 60 to 86% respectively 1,12 . While for early RA, the sensitivity of RF is 57% and its low specificity ranges between 70-85% 12 . On the other hand, it is estimated that about 70% of joints may be destroyed during the second year of disease onset 2 .…”
Section: Introductionmentioning
confidence: 99%